Adhesion science - Comyn, John (Royal Society of Chemistry paperbacks., 1997)
The use of adhesives is widespread and growing, and there are few modern artefacts, from the simple cereal packet, to the jumbo jet, that are without this means of joining. Adhesion Science provides an illuminating account of the science underlying the use of adhesives, a branch of chemical technology which is fundamental to the science of coatings and composite materials and to the performance of all types of bonded structures. This book guides the reader through the essential basic polymer science, and the chemistry of adhesives in use at present. It discusses surface preparation for adhesive bonding, and the use of primers and coupling agents. There is a detailed chapter on contact angles and what can be predicted from them. A simple guide on stress distribution joints and how this relates to testing is included. It also examines the interaction of adhesives and the environment, including an analysis of the resistance of joints to water, oxygen and ultra-violet light. Adhesion Science provides a comprehensive introduction to the chemistry of adhesives, and will be of interest not only to chemists, but also to readers with a background in physical or materials science.